2016
DOI: 10.1016/j.bios.2015.07.031
|View full text |Cite
|
Sign up to set email alerts
|

Glyconanomaterials for biosensing applications

Abstract: Nanomaterials constitute a class of structures that have unique physiochemical properties and are excellent scaffolds for presenting carbohydrates, important biomolecules that mediate a wide variety of important biological events. The fabrication of carbohydrate-presenting nanomaterials, glyconanomaterials, is of high interest and utility, combining the features of nanoscale objects with biomolecular recognition. The structures can also produce strong multivalent effects, where the nanomaterial scaffold greatl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
38
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 47 publications
(38 citation statements)
references
References 251 publications
0
38
0
Order By: Relevance
“…Nature uses a well-known strategy, named multivalent effect, to increase this low affinity by gathering multiple copies of sugars to achieve a global binding potency toward their receptors higher than that for the sum of the monovalent interactions [27]. Inspired by this natural approach, a vast number of structures decorated with multiple carbohydrate moieties have been tested as potential theranostic agents in biosensing and biomedicine [22,28,29].…”
Section: Introductionmentioning
confidence: 99%
“…Nature uses a well-known strategy, named multivalent effect, to increase this low affinity by gathering multiple copies of sugars to achieve a global binding potency toward their receptors higher than that for the sum of the monovalent interactions [27]. Inspired by this natural approach, a vast number of structures decorated with multiple carbohydrate moieties have been tested as potential theranostic agents in biosensing and biomedicine [22,28,29].…”
Section: Introductionmentioning
confidence: 99%
“…7 MSNs are generally prepared from alkoxysilanes or silicates using a base or acid catalyst, and an organic surfactant or a block copolymer as the structure-directing template. 8 Recent work have shown that the particle shape plays a critical role in successfully realizing many of the aforementioned applications.…”
mentioning
confidence: 99%
“…This review does not extend to coverage of the formation and modification of self-assembled monolayers on NPs and bioconjugation techniques for glycan immobilization and controlling interfacial glycan density. The reader is directed towards an excellent review study [ 44 ] and a book chapter [ 43 ].…”
Section: Glycan-functionalized Nanoparticles (Nps)mentioning
confidence: 99%